Research on decision-making of water diversion supply chain considering both social welfare and water quality utility - Jiao, Hongbo; Zhang, Jiachao; Li, Yinan; Cheng, Liming; Chen, Yongrui; Zhu, Hanyu (Frontiers in Earth Science, 2023)
When water diversion projects become important parts of the water network around the world, the effective operation and management of the projects play important roles in giving full play to the optimal allocation of water resources. For the operation and management of water transfer, the decision of water supply chain under the scenario of economic benefit, producer surplus and water quality utility should be considered simultaneously. According to the idea of supply chain, this paper regards water transfer operation management as a water supply chain composed of water transfer companies, water supply companies and consumers. From the perspective of social welfare and water quality utility, a comprehensive optimization and coordination decision model for water transfer is proposed. Taking the South-to-North Water Diversion Project as the research object, the cost-sharing contract is designed, and the Stackelberg game method is used to optimize the decision-making and coordination of the water supply chain. The results show that when the concern coefficient and the cost-sharing ratio are valued within a given feasible value region, the profits of both the water transfer company and the water supply company can be Pareto improved. The feasible value interval of the concern coefficient decreases with the increase of the cost-bearing proportion. When the concern coefficient increases, the profit of water transfer company decreases, while the profit of water supply company, water quality, consumer surplus, water quality utility and utility of the water transfer company increase gradually. The results provide valuable references for water transfer decision-making.